Design of Handoff Communication Sequence Architecture in LoRa Networks - Manalu, Istas Pratomo; Simatupang, Frengki; Sinambela, Eka Stephani; Sigiro, Marojohan Mula Timbul; Wowiling, Gerry Italiano; Silalahi, Sari Muthia (Piston: Journal of Technical Engineering, 2025)
Technological advances have driven the development of IoT-based object tracking systems, where LoRa is an ideal wireless technology due to its long range and low power consumption. Challenges in implementing LoRaWAN, particularly its role in the handoff process between gateways that can disrupt communication, can be overcome by developing a more efficient handoff method. For this reason, this study presents the design of Handoff communication for the LoRa Network. We use two gateways and one transmitter node. The gateway node consists of a LoRa module and an ESP32, while the Transmitter consists of a LoRa module, an Arduino Nano, and a GPS sensor. The RSSI parameter is a determining factor in transferring connectivity paths from GW A or GW B, as it provides an RSSI threshold value of -100 dBm. We successfully designed handoff communication at each Node and conducted a mini-test. The test results show that LoRa can implement handoff techniques at a distance of 0-500 meters. This indicates that the node is in closer range to GW A. The RSSI value of GW1 is in the range of -52 dBm to -98 dBm, while the RSSI of GW2 is in a much weaker range, which is around -120 dBm to -100 dBm. As the distance increases, the RSSI value of GW1 shows a significant decrease, while the RSSI of GW B actually increases. At a distance of approximately 250 meters, there is an intersection point between the RSSI values of the two gateways, marking the optimal handoff point. Thus, this system is able to select the best gateway, provide redundancy, check gateway availability before handoff, and handle handoff failures, thereby improving the efficiency and effectiveness of data delivery.